(3Odjd GdeSJNOe GdYQHj aj GdHQeLjGJ GdMOjKI (B:s (3fXGe GdJTZjd Ee ES OhS (BMS-DOS /s - (3YeQ ecOGTjs ((3HjQhJ (B:s (3OGQ GdQGJH GdLGeYjI,s, 1988)
(3GdceHjhJQ GdTNUj hehGQOg GdCSGSjI(B.s
Keywords: (3eGjcQhShaJ OhS (B((3eda MGShH(B)s; (3fXe GdJTZjd (B((3MGSHGJ EdcJQhfjI(B)s -- (3HQGeL GdMGShH(B.s